Self-control cycles - Shinsuke Ikeda; Takeshi Ojima (Osaka University, Institute of Social and Economic Research (ISER), 2025)
Consumers often exhibit behavioral cycles with alternating abstinence and indulgence over time. In the framework of tempting good consumption under limited willpower, we develop a simple model of the self-control cycles. To do so, based on the empirically relevant property of self-control, we incorporate two countervailing effects that self-control behaviors have on willpower with different delays. First, exercising self-control as of restraining tempting consumption depletes willpower in the next instant, and thereby reduces mental capital available for self-control thereafter. Second, as the self-control experience is accumulated, the consumer's willpower is gradually enhanced. The resulting predator-prey type dynamics in consumers' cognitive mechanics lead to cycles in tempting good consumption. The self-control cycles occur when (i) the self-control cost reducing effect of willpower and (ii) the willpower enhancing effect of self-control are both sufficiently strong.
Keywords: 330; Self-control; cycle; temptation; willpower; malleability; consumption